Assessment of petroleum biodegradation for Bacillus toyonensis by the using redox indicator 2,6 dichlorophenol indophenol - Ferdyanne Beatriz Sabóia Peixoto; Jean Charles da Cunha Peixoto; Diana Cibelli Lucas Motta; Ana Teresa Miranda Peixoto; José Odair Pereira; Spartaco Astolfi-Filho (Acta Scientiarum. Biological Sciences, 2018)
Petroleum degrading microorganisms have been isolated from different environments with the purpose of being used in bioremediation processes in areas impacted by petroleum spills. The objective of this study was to evaluate the ability of Bacillus toyonensis AM07 strain to metabolize petroleum compounds. The strain was isolated from the effluent dike of the Urucu Petroleum Province, Coari - Amazonas, Brazil. The degrading activity of B. toyonensis was evaluated by the colorimetric method using the redox indicator 2,6-dichlorophenol indophenol (DCPIP). Thus, the microorganism was inoculated into minimal medium with DCPIP, and with petroleum as the sole carbon source. The degradation potential of the microorganism was found by changing the DCPIP staining and absorbance readings 600nm. The results obtained demonstrated that the bacterial strain was able to degrade petroleum by altering the color of the medium from blue to colorless and by reducing the concentration of the indicator in the absorbance readings. B. toyonensis AM07 strain has shown good performance in the petroleum degradation assays and may be used in the future in remediation technologies for hydrocarbon impacted environments.